Evaluasi Nilai Nutrisi dan Kecernaan In Vitro Pelepah Kelapa Sawit (Oil Palm Fronds) yang Difermentasi Menggunakan Aspergillus niger dengan Penambahan Sumber Karbohidrat yang Berbeda - Sitti Wajizah; Samadi Samadi; Yunasri Usman; Elmy Mariana (Agricultural Faculty, 2015)
(The evaluation of nutritive value and In Vitro digestibility of oil palm fronds through fermentation by using Aspergillus niger with different soluble carbohydrate sources)ABSTRACT. Oil palm frond (OPF) is one of potential sources of alternative feed, but has limited use due to high crude fiber and low crude protein contents. Fermentation is one of the methods widely applied to improve nutritive value of animal feed. The purpose of this research is to increase nutritive value of fermented oil palm fronds by adding different soluble carbohydrate source into fermentation media. The results of the experiments indicated that fermented oil palm fronds by Aspergillus niger had a significant effect (P0,05) on the content of crude protein, crude fiber, and ash. Generally, fermented oil palm fronds with different soluble carbohydrate was able to increase the content of crude protein of oil palm fronds, but not optimal yet in reducing the crude fiber content of fermented substrate. However, the addition of rice bran on the fermentation medium showed the best results, characterized by increasing crude protein and decreasing crude fiber contents as well as improved dry matter and organic matter digestibility, reflected in high concentration of VFA.